Risk factors for surgical site infection after craniotomy for meningioma resection in a tertiary hospital in China - Hong Wang; Yu-Lu He; Yin Gao; Xing-Rong Gao; Li-Yuan Sun; Ji-Cheng Yan; Qun Lu; Kai-Wen Ni (World Journal of Clinical Oncology, 2026)
BACKGROUND Meningioma is the most common intracranial neoplasm and carries a non-negligible surgical site infection (SSI) risk (reported incidence: 4%-6%) despite its clean-wound classification. Most existing studies enroll heterogeneous neurosurgical cohorts spanning vascular, traumatic, and biologically distinct tumor entities, even though meningioma itself is an independent SSI risk factor, which calls for disease-specific investigation. Preoperative host physiologic reserve indices have shown prognostic value across oncology and neurosurgery, yet remain unevaluated as predictors of SSI after meningioma resection in Chinese cohorts. We hypothesized that precisely measured surgery time and preoperative immune-nutritional status are associated with SSI risk in this population. AIM To examine modifiable factors associated with SSI after meningioma resection, focusing on precisely measured surgery time and preoperative immune-nutritional indices. METHODS A 1:4 matched case-control study was conducted at a tertiary neurosurgical center between January 2022 and November 2025, with matching on age, sex, and year of surgery. SSI was defined according to United States Centers for Disease Control and Prevention criteria. Surgery time was defined as the interval from skin incision to wound closure. Preoperative indices, including neutrophil-to-lymphocyte ratio (NLR), prognostic nutritional index, nutritional risk index, and modified frailty index, were extracted from routine clinical assessments. Least Absolute Shrinkage and Selection Operator regression followed by conditional logistic regression was used, with restricted cubic splines examining the dose-response relationship between surgery time and SSI risk. RESULTS Longer surgery time was independently associated with SSI (odds ratio = 1.824 per hour; 95% confidence interval: 1.405-2.369), with a threshold of 3.04 hours beyond which SSI risk increased 5.7-fold. Preoperative NLR was also independently associated with SSI risk (odds ratio = 1.081; 95% confidence interval: 1.007-1.159). The model showed good discrimination (area under the curve = 0.828) with acceptable calibration. CONCLUSION Longer surgery time and elevated preoperative NLR are associated with SSI after meningioma resection. A 3.04-hours threshold offers a practical criterion for prospective risk stratification.